SKRINING FITOKIMIA DAN UJI TOKSISITAS PADA DAUN TERAP (Artocarpus elasticus) DENGAN METODE BRINE SHRIMP LETHALITY TEST (BSLT) - Mahardika Nastiti; Erwin Erwin; Irawan W. Kusuma (PROSIDING SEMINAR KIMIA, 2017)
A research to find out the secondary metabolite compounds contained in theleaves of terap (Artocarpus elasticus) and its toxicity of terap leavesextract has been done by using Brine Shrimp Lethality Test (BSLT) method. Toxicity was conducted for prawn Artemia salina Leach of 48 hours age. Toxicity data were obtained from Lethal Concentration 50% (LC50) with percentage of death of prawn larva and counted by probit analysis SAS. The result showed that 5thn-hexane fraction was more toxic than another extract with LC50 values 71.887 ppm and furthermore, the bioactive compound of 5thn-hexane fraction was probably to be either steroid compound. Keywords: Artocarpus elasticus, Phytochemical, Toxicity